(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The article deals with the issues of the impact of melioration on agricultural lands. The melioration conditions of the lands of the regions of Uzbekistan are analyzed. Practical recommendations for increasing farmland with the help of optimal management are given.